Validation and test-retest reliability of the Royal Free Interview for Spiritual and Religious Beliefs when adapted to a Greek population - Sapountzi-Krepia, Despina; Sgantzos, Marcos N.; Kotrotsiou, Evangelia; Roupa-Darivaki, Zoe; Sotiropoulou, Kalliope; Ntourou, Ioanna; Dimitriadou, Alexandra; Raftopoulos, Vasilios (My University, 2005)
Background: The self-report version of the Royal Free Interview for Religious and Spiritual Beliefs has been confirmed as a valid and reliable scale, assessing the manner and nature in which spiritual beliefs are expressed. The aim of the present study was to evaluate the test-retest reliability and psychometric properties of the Greek version of the Royal Free Interview for Religious and Spiritual Beliefs. Methods: A total of 209 persons (77 men and 132 women) with a mean age of 28.33 ± 9.44 years participated in the study (test group). We subsequently approached 139 participants of the test group with a mean age of 28.93 ± 9.60 years, who were asked to complete the Royal Free Questionnaire a second time two weeks later (retest group). Results: The vast majority of participants (58.9%) reported both a religious and a spiritual belief, compared to 52 (25.1%) who told of a religious belief only. The internal consistency of the spiritual scale for the test group proved to be good, as standardized inter-item reliability / Cronbach's alpha was 0.83. Item-total correlations ranged from 0.51 to 0.73. They indicated very good levels of differentiation, thus showing that the questions were appropriate. Internal consistency of the spiritual scale for the retest group proved as good as for the test group. Standardized inter-item reliability / Cronbach's alpha was 0.84. Item-total correlations ranged from 0.52 to 0.75. The Pearson correlation coefficient for the total test-retest score of the spiritual scale was 0.754 (p < 0.001). Conclusion: The Greek version of the Royal Free Interview for Religious and Spiritual Beliefs is reliable and thus suitable for use in Greece.
Keywords: Mental disorders; Open access publishing